Descriptive analysis of COVID-19 in Manokwari Regency, West Papua Province (March 2020-October 2021) - Damanik, Brema J.K. (BKM Public Health and Community Medicine, 2021)
Objective: The study is to provide a descriptive analysis Covid-19 in Manokwari Regency in March 2020 until October 2021. Method: Analysis in the study uses secondary data from Manokwari Health Office “Pelaporan Daftar Kasus Terkonfirmasi Covid-19 di Kabupaten Manokwari 2020-2021”. The study uses univariate analysis which aims to describe the description of Covid-19 cases in Manokwari Regency in 2020-2021. Results: The study found Covid19 case in Manokwari Regency was 8.709 case. With the distribution of cases in West Manokwari district (49,30%), South Manokwari district (22,79%), Masni district (11,78%), Prafi district (4,34%), outside the area Manokwari (4,30%) East Manokwari district (4,10%), Sidey district (1,70%), Warmare district (1,50%), North Manokwari district (0,11%), and Tanah Rubuh district (0,03%). The cases recovered (99,03%) cases died (0,83%) and cases under treatment (0,12%). There was no significant difference by sex. The adult group (26-45 years) is the most positive Covid-19 (47,73%), teenager group (12-25 years) was 23,44%, elderly group (>45 years) was 20,83%,child (6-11 years) was 4,46% and child under five years old was 3,51 %. Conclusions: The recovery rate for Covid-19 cases in Manokwari Regency is good. Where the case of the spread of Covid-19 in center of the capital of Manokwari (West Manokwari district). There is no difference in Covid-19 cases by sex. The adult grup and teenager group are the most affected by Covid-19. Futher research can be done to see the relationship of risk factors to Covid-19 in Manokwari Regency.